Counter-Pandemic Vector of Remote Learning for University Students: Risks and Benefits of Educational Process Large-Scale Digitalization - Tavstukha, Olga G. (2021)
The relevance of this study is due to the challenges of the global pandemic, which has led to the large-scale development of education digitalization. In this regard, this article is devoted to revealing the features of remote learning in the context of a global pandemic, identifying the risks and benefits of digital learning. The article reveals the discursive content of the counter-pandemic vector of distance learning for University students; defines the classification of risks and advantages of large-scale digitalization of students’ remote learning. Based on the results of the study, the authors justified the consolidated model of students distance learning, the counter-pandemic vector of which is a large-scale digitalization of the University educational process. The effectiveness of the model is proved by the results of its use in the process of large-scale digitalization of students’ remote learning in the context of a global pandemic. The materials of the article have practical application and can be useful in the development and implementation of digital educational complexes. They are recommended to teachers and students of the University, methodologists, curators, Tutors.